Narrowing the gap between the number of athletes who dope and the number of athletes who are caught: scientific advances that increase the efficacy of antidoping tests - Botrè, F.; de la Torre, X.; Donati, F.; Mazzarino, M. (British Journal of Sports Medicine, 2014)
The analytical methods developed and applied by the antidoping laboratories have been continuously evolving over the past 50 years, with the aim of keeping pace with the constant evolution of doping strategies. Despite this, the number of adverse analytical tests reported worldwide by the network of the WADA-accredited laboratories still seems to underestimate the actual number of doped athletes.We investigate the most likely causes for this gap between the likely doping rate and the detection of athletes with positive doping tests. We consider laboratory and non-laboratory reasons that contribute to this gap. More specifically, laboratory issues are focused not only on those doping practices that may still be `invisible` at the time of a doping test, but also on the possible role of non-conventional masking strategies. These include (1) the intake of banned drugs by specific novel drug delivery systems and (2) the coadministration of prohibited and non-prohibited drugs, taking advantage of the capacity of the latter to affect the metabolism, and consequently the detection, of the former. Non-laboratory issues include the lack of a sufficient level of `intelligent testing`, with the result that, even in the cases of doped athletes, the biological samples delivered to the antidoping laboratories for analysis may not contain those target analytes whose detection (and if necessary quantification above a decision limit) constitutes an adverse analytical finding. We present proposals to improve the efficacy of the doping control policies based on the analysis of biological samples and suggest how to constantly keep up with the continuous developments of new forms of doping.